Valuasi ekonomi sumber daya alam kawasan hutan lindung Siregol di Desa Sirau, Kecamatan Karangmoncol, Purbalingga - Ageng Pramestyan (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
This research is about the valuation of natural resources, especially the direct use value of the Glagah Arjuna (Themmeda fillosa) plant. The objective of this research is to determine the value of the natural resources of the Siregol Protected Forest area in Sirau Village, Karangmoncol District, Purbalingga Regency. The method used in this research is the Production Function Approach method and the data collection techniques use interview techniques (primary data) and literature study (secondary data). The population taken in this study were farmers of Glagah Arjuna Sirau Village, Karangmoncol District, Purbalingga Regency, by taking a sampling of 4 respondents from the total Glagah Arjuna farmers in Sirau Village, the data obtained were analyzed using descriptive qualitative. The results of the research conducted, obtained the total economic value of the ecosystem of the Siregol Protected Forest area specifically for the cultivation of Glagah Arjuna plants of Rp. 3,036,262,500.00. The potential value of natural resources obtained can be increased considering that not all of the Siregol Protected Forest area has been utilized.